2021
DOI: 10.1016/j.amsu.2021.102773
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Platelet-Rich Plasma and Stromal Vascular Fraction combination on Epidermal Growth Factor serum level for anal trauma healing in the Wistar rat model

Abstract: Introduction Stromal Vascular Fraction cells (SVFs) and Platelet Rich Plasma (PRP) are clinically proven to aid in cell regeneration and wound healing. The healing effects can be measured by the level of Epidermal Growth Factor (EGF). This study aims to investigate the effect of an SVFs and PRP combination on EGF levels in the anal trauma model. Method Twenty-eight adult Wistar rats were divided into 3 groups: Group A consisted of healthy rats as a normal control group;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Previous studies have suggested that wound healing will be enhanced by PRP and SVF treatment. 12,14 While the mechanism is not fully understood, its potential components and…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that wound healing will be enhanced by PRP and SVF treatment. 12,14 While the mechanism is not fully understood, its potential components and…”
Section: Discussionmentioning
confidence: 99%
“…The anal trauma model used in this study was adapted from Trebol et al 12,14,16 Sacrificing Procedure Rats from Groups A and B were sacrificed on days 1, 7, and 14 post-treament. All rats were anaesthetized with ether before sacrificed.…”
Section: Anal Trauma Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of experimental rats required was 10, based on the Federer formula [ 8 ]. The criteria for inclusion were (1) rats (Rattus Norvegicus) of the Wistar male strain, (2) aged 2–3 months, (3) weighing 150–200 g, and (4) in good health.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, Sirowanto et al found that local injection of an SVF and PRP combination within an anal trauma model increased the epidermal growth factor (EGF) level during the healing process [ 22 ]. In this study, we aim to determine the effect of an SVF and PRP combination on bFGF levels during anal trauma healing.…”
Section: Introductionmentioning
confidence: 99%